Relationship between body volume and rib eye area in Colombian buffalo cattle - Sebastián Pineda-Sierra; Divier Antonio Agudelo-Gómez; Edison Julián Ramírez-Toro; Diana Carolina Solano-Suárez; Andrés Felipe Pérez-Rojo (Revista Científica)
In genetic improvement programs, one of the key aspects is the selection of animals with high genetic potential for economically important traits. Rib eye area (REA) is important due to its positive relationship with carcass yield. REA is traditionally measured on the animal’s carcass or using a real-time ultrasound tool. Therefore, searching for alternatives that facilitate REA estimation is crucial for livestock producers. This study aimed to estimate the relationship between body volume and REA in Murrah buffalo. Data from 24 Murrah buffaloes participating in the VI performance test were used. The test lasted for 252 days, including an initial adaptation period. Morphometric and ultrasound measurements were taken every 28 days to assess the animals’ development using a zoometric cane and an Esaote MyLab ultrasound scanner device equipped with a linear transducer (3.5-MHz; 18 cm). Analysis of variance was conducted to identify the effect on REA and correlations between significant variables and REA were estimated. A regression model with significant variables from the ANOVA was used to identify the proportion of each variable’s effect on REA. To estimate body volume (BV), a cone trunk formula was applied using the following measurements: thoracic perimeter (TP), abdominal perimeter (AP), inguinal perimeter, and sacrum-croup length. Analysis of variance was performed to determine the effect of morphometric measurements on REA. A highly significant effect was found for weight, height, and BV. Although BV was highly significant, the independent variables included in the calculation were not significant. The correlation between weight, height, and BV with REA was 0.77, 0.50, and 0.67, respectively. The regression analysis indicated that for every unit change in weight, height, and BV, REA increases by 0.07, 0.05, and 42.37 cm3, respectively. A regression model can be used to estimate REA and assist in the selection process of buffaloes for future breeding when real-time ultrasound is unavailable.